Data Security Analysis of Chatting Applications Using End-to-End Encryption - Intan Juniarmi (Pt. Anagata Sembagi Education, 2024)
This research aims to analyze data security in chat applications by applying end-to-end encryption techniques. The research method used is a literature study and qualitative analysis of chat applications that use end-to-end encryption. The results show that the implementation of end-to-end encryption in chat applications is effective in maintaining the confidentiality of user data, securing messages from hacking and data interception attacks, and increasing user security awareness. However, this study also identified some challenges related to application performance and encryption key management. Therefore, this study recommends the development of a more efficient and comprehensive end-to-end encryption technology to maximize user data security in chat applications.